Detoxification of Aflatoxin B1 and Fumonsinin B1 in Broiler chickens by grape seed extract and hydrated sodium calcium aluminosilicate - Hassan, Reda; Abu El-hassan, El-Sayed; Farouk, Zeinab; Gorgy, Michael; El-Gbaly , Mahmoud (Journal of King Abdulaziz University-Meteorology Environment and Arid Land Agriculture Sciences, 2023)
A feeding trial was conducted on commercial broilers for a period of 35 days to determine the individual effects of aflatoxin B1 (AFB1) and Fumonsinin B1 (FB1) toxins on performance, organ weights and immune status. The efficacy of dietary grape seed extract (GSE) and hydrated sodium calcium aluminosilicate (HSCAS) in preventing the adverse effects of AFB1 and FB1 toxin was also evaluated. Seven dietary treatments were tested on 420 commercial broiler chickens divided randomly into 42 replicates of 10 chicks each. the nutritional treatments: (1) control (non-contaminated diet); (2) non contaminated diet + 1mg/kg of AFB1; (3) non-contaminated diet + 400 mg/kg FB1 ; (4) 1 mg/kg AFB1 + 500 mg/kg GSE; (5) 1 mg/kg AFB1 + 5 g/kg HSCAS; (6) 400 mg/ kg FB1 + 500 mg/kg GSE; and (7) 400 mg/kg FB1 + 5 g/kg HSCAS. Feed intake and body weight gain were recorded weekly. On the 35th day, organ morphology and antibody titers for infectious bursal disease (IBD) and Newcastle disease (ND) were assessed. Individually, AFB1 and FB1 reduced weight gain while raising the feed conversion ratio (FCR) and mortality rate (p ≤ 0.05). AFB1 alone (p ≤ 0.05) raised the weights of the liver, kidney, gizzard, and spleen while decreasing the weights of the thymus and bursa. FB1 increased liver and gizzard weights and decreased thymus weight. Individual doses of AFB1 and FB1 substantially impacted NDV and IBD titers. GSE supplementation increased weight gain, enhanced feed conversion efficiency, and restored organ weights (p ≤ 0.05). With the addition of GSE, antibody titers against NDV and IBD were dramatically increased. Adding HSCAS increased body weight gain and restored organ weights in birds fed AFB1 alone but not in birds given FB1 (p ≤ 0.05). FCR in groups fed toxins was unaffected by HSCAS addition. Adding HSCAS (p ≤ 0.05) increase antibody titers against NDV and IBD. In conclusion, mycotoxins cause adverse effects, especially aflatoxin B1, which is more severe than Fumonsinin B1. Whereas HSCAS (5 g/kg diet) is effective solely against AFB1, GSE (500 mg /kg diet) prevents the individual toxicity of AFB1 and FB1 in commercial broilers.